-4(p-7)-8=5p+11

Simplify each term.

Apply the distributive property.

-4p-4⋅-7-8=5p+11

Multiply -4 by -7.

-4p+28-8=5p+11

-4p+28-8=5p+11

Subtract 8 from 28.

-4p+20=5p+11

-4p+20=5p+11

Subtract 5p from both sides of the equation.

-4p+20-5p=11

Subtract 5p from -4p.

-9p+20=11

-9p+20=11

Subtract 20 from both sides of the equation.

-9p=11-20

Subtract 20 from 11.

-9p=-9

-9p=-9

Divide each term in -9p=-9 by -9.

-9p-9=-9-9

Cancel the common factor of -9.

Cancel the common factor.

-9p-9=-9-9

Divide p by 1.

p=-9-9

p=-9-9

Divide -9 by -9.

p=1

p=1

Solve for p -4(p-7)-8=5p+11